Spin–Orbit TDDFT Electronic Structure of Diplatinum(II,II) Complexes - Záliš, Stanislav; Lam, Yan-Choi; Gray, Harry B; Vlček, Antonín (Inorganic chemistry, 2015)
[Pt2(μ-P2O5H2)4]4– (Pt(pop)) and its perfluoroborated derivative [Pt2(μ-P2O5(BF2)2)4]4– (Pt(pop-BF2)) are d8–d8 complexes whose electronic excited states can drive reductions and oxidations of relatively inert substrates. We performed spin–orbit (SO) TDDFT calculations on these complexes that account for their absorption spectra across the entire UV–vis spectral region. The complexes exhibit both fluorescence and phosphorescence attributable, respectively, to singlet and triplet excited states of dσ*pσ origin. These features are energetically isolated from each other (∼7000 cm–1 for (Pt(pop-BF2)) as well as from higher-lying states (5800 cm–1). The lowest 3dσ*pσ state is split into three SO states by interactions with higher-lying singlet states with dπpσ and, to a lesser extent, pπpσ contributions. The spectroscopically allowed dσ*pσ SO state has ∼96% singlet character with small admixtures of higher triplets of partial dπpσ and pπpσ characters that also mix with 3dσ*pσ, resulting in a second-order 1dσ*pσ–3dσ*pσ SO interaction that facilitates intersystem crossing (ISC). All SO interactions involving the dσ*pσ states are weak because of large energy gaps to higher interacting states. The spectroscopically allowed dσ*pσ SO state is followed by a dense manifold of ligand-to-metal–metal charge transfer states, some with pπpσ (at lower energies) or dπpσ contributions (at higher energies). Spectroscopically active higher states are strongly spin-mixed. The electronic structure, state ordering, and relative energies are minimally perturbed when the calculation is performed at the optimized geometries of the 1dσ*pσ and 3dσ*pσ excited states (rather than the ground state). Results obtained for Pt(pop) are very similar, showing slightly smaller energy gaps and, possibly, an additional 1dσ*pσ – 3dσ*pσ second order SO interaction involving higher 1dπpσ* states that could account in part for the much faster ISC. It also appears that 1dσ*pσ → 3dσ*pσ ISC requires a structural distortion that has a lower barrier for Pt(pop) than for the more rigid Pt(pop-BF2).